Effect of Total versus Partial Assisted Hatching on the Clinical Pregnancy Rates in Assisted Reproduction Technology - Bilgic, Bulent Emre; Ozkaya, Enis; Yayla Abide, Cigdem; Kayatas Eser, Semra; Sanverdi, Ilhan; Kutlu, Tayfun (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: The objective of this study was to investigate the effect of total or partial assisted hatching on the clinical pregnancy rates in assisted reproduction technology. Study Design: This was a case-control study conducted from the beginning of January 2016 to the end of June 2017. A total of 404 cycles were included in this case-control study. Study population was divided into 3 groups: Group 1: Partial assisted hatching (n=118), Group 2: Total assisted hatching (n=81) and Control group (n=205). Results: In women of all ages, clinical pregnancy rates were similar between groups with total or partial assisted hatching compared to control group (p>0.05). The rates were also similar in subgroups of women with blastocyst or cleavage stage embryo transfers (p>0.05). Partial or total embryo hatching did not result in favorable outcome compared to control group either in women over 35 or younger than 35 years of age (p>0.05). In whole study group pregnancy rate was significantly higher in group with blastocyst stage embryo transfers (22.4 % versus 48.8%, p<0.05) Conclusion: Partial or total assisted hatching do not have any impact on the clinical pregnancy rates, no significant impact was determined in subgroup of women either.